Simulation Study of Multi-wire front Contact Grids for Silicon Solar Cells. (August 2015) - Nicolai, Massimo; Zanuccoli, Mauro; Magnone, Paolo; Galiazzo, Marco; Tonini, Diego; Bertazzo, Matteo; Sangiorgi, Enrico; Fiegna, Claudio
Abstract: Multi-wire (MW) front-contact schemes represent a promising alternative to standard H-pattern structure with ribbon busbar (BB) in silicon solar cells. In the case of MW schemes, busbar are replaced by copper wires. MW have been demonstrated to enhance the photo-generation with respect to a standard H-pattern structure with ribbon busbar when solar cells are encapsulated and assembled in modules. However, the influence of the geometrical and optical properties of the encapsulation layers as well as of wires on the optical effective shading is not exhaustively treated by the literature. In this work, we have performed electro-optical simulations of MW and BB based solar cells in order to calculate the effective optical shading factor, the enhancement of conversion efficiency and the saving of contact-paste, with respect to the BB design. Specifically, we have studied by means of a ray-tracing simulation tool the significant impact of the front contact grid geometry, of the encapsulation layer thickness and of the optical properties of the cell front interface on the effective optical shading. The calculated values of effective optical shading are used to determine the enhancement of the figures of merit and the paste saving with respect to the reference silver BB scheme. On the basis of our calculations the adoption of optimized MW designs may enhance the conversion efficiency up to 0.5%abs, allowing paste saving up to 50 mg per cell.